2018
DOI: 10.1142/s0219876218500299
|View full text |Cite
|
Sign up to set email alerts
|

Application of Smoothed Finite Element Method to Two-Dimensional Exterior Problems of Acoustic Radiation

Abstract: In this work, the smoothed finite element method using four-node quadrilateral elements (SFEM-Q4) is employed to resolve underwater acoustic radiation problems. The SFEM-Q4 can be regarded as a combination of the standard finite element method (FEM) and the gradient smoothing technique (GST) from the meshfree methods. In the SFEM-Q4, only the values of shape functions (not the derivatives) at the quadrature points are needed and the traditional requirement of coordinate transformation procedure is not necessar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 75 publications
(24 citation statements)
references
References 89 publications
1
23
0
Order By: Relevance
“…In addition, Edmundo Lavia et al derived a computational method to calculate the exact solution for liquid spheroid which agrees with reported predicted results obtained through approximated solution for far-field and near-field regimes [8]. Based on the discussions of the scattering of the fluid spheroid, the acoustical radiation force of a fluid spheroid or a liquid-filled spherical shell could be obtained, which could benefit the application of the biomedical, drug deliver, biochemistry and other areas [9].…”
Section: Introductionsupporting
confidence: 68%
“…In addition, Edmundo Lavia et al derived a computational method to calculate the exact solution for liquid spheroid which agrees with reported predicted results obtained through approximated solution for far-field and near-field regimes [8]. Based on the discussions of the scattering of the fluid spheroid, the acoustical radiation force of a fluid spheroid or a liquid-filled spherical shell could be obtained, which could benefit the application of the biomedical, drug deliver, biochemistry and other areas [9].…”
Section: Introductionsupporting
confidence: 68%
“…According to the periodicity of cavity, the model of anechoic coatings can be simplified to the unit cell to analyze the acoustic scattered properties by the Bloch theorem [6]. Therefore, the following periodic boundary conditions should be satisfied [1]:…”
Section: Discussionmentioning
confidence: 99%
“…Anechoic coatings can reduce the reflection of sound waves, so it is necessary for researchers to study the acoustic scattering properties of the shell structures covered by anechoic coatings. The Finite Element Method (FEM) is most popular numerical techniques for handling acoustic computation [1,2]. Kim established a numerical methodology based on Kirchhoff approximation to simulate the acoustic target strength (TS) of a submarine attached with anechoic coatings, and the finite element method is applied to calculate the acoustic pressure reflection coefficient [3].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is necessary to obtain their approximate solutions by using some efficient numerical methods. The finite difference method (FDM) and the finite element (FEM) techniques [8] are classical tools for the numerical modeling of the ADR problem. A detailed review of the classic methods involving FEMs and FDMs can be found in [9].…”
Section: Introductionmentioning
confidence: 99%